Calidad del servicio y la fidelización de los clientes de las empresas que ofrecen el servicio de internet en el cantón La Maná. - Coba Baño, Verónica Silvana (2022)
With the arrival of internet, communication barriers decrease and give a way to the use of digital tools. In an increasingly competitive market, full of demanding consumers, the quality of internet service is essential, so resulting in customer loyalty. After the COVID-19 pandemic, virtual normality is presented with the respective connectivity problems. The companies that offer internet service have a fundamental role because the user can carry out activities such as: teleworking, virtual classes and entertainment. The research project aims to determine the relation between the quality of service and customer loyalty at the 8 companies that provide internet service in La Maná canton. The research is a documentary, descriptive, and field type. The population in study corresponds to 15,050 customers and the sample is 389 internet users. The results: speed, price, customer service, coverage, innovation, benefits, and promotions reflect the elements of quality that users take into account when contracting an internet service. 68.38% of users choose speed as an important element when contracting an internet service, as opposed to price 24.42%. Enlace Net has 76.92% of users that agree with the quality of the service which is provided by this company, this fact stands out from its competitors. The company that has the most average of loyal customers is Pato Net with 74.63% of customers who specify that they would never change the company. To test the relation between the quality of service variable and customer loyalty, the statistical analysis of bivariate correlations was used in the SPSS program. The result was a p-value of 0.001, it means that there is a significant relation between quality of service and customer loyalty. To conclude, the correlation coefficient is 0.875, this relation is direct and positive, so indicating that a higher quality of service, a greater customer loyalty.